2016
DOI: 10.1111/eve.12587
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and morphological sequelae to repeated testicular biopsies in stallions in relation to the lateral branching of the testicular artery

Abstract: Summary The objectives of this study were to investigate the sequelae to repeated testicular biopsies in stallions and to determine if arterial injuries can be prevented. This study was part of a larger project focused on the antispermatogenic effects of an oral contraceptive compound, RTI‐4587‐073(l), which was given to 3 mature Miniature horse stallions, while another 3 received a placebo treatment. Testicular biopsies were taken once before treatment and 3 times after treatment. They were obtained from alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Different biopsy techniques have been used in stallions, such as the open method, split-needle biopsy, and needle-punch biopsy. The size of the biopsy instrument used should be chosen according to the size of the testis, and it varies between the recommended 14 g for adult stallions [ 28 ] to 18 g for miniature stallions [ 29 ]. The most commonly used method is the split-needle biopsy (Biopty, Tru-Cut) [ 28 ] ( Figure 5 ).…”
Section: Examination Techniques Of the Stallion Scrotum And Its Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Different biopsy techniques have been used in stallions, such as the open method, split-needle biopsy, and needle-punch biopsy. The size of the biopsy instrument used should be chosen according to the size of the testis, and it varies between the recommended 14 g for adult stallions [ 28 ] to 18 g for miniature stallions [ 29 ]. The most commonly used method is the split-needle biopsy (Biopty, Tru-Cut) [ 28 ] ( Figure 5 ).…”
Section: Examination Techniques Of the Stallion Scrotum And Its Contentmentioning
confidence: 99%
“…The most commonly used method is the split-needle biopsy (Biopty, Tru-Cut) [ 28 ] ( Figure 5 ). Because of the high vascular component of testes, color Doppler ultrasonography can help to identify a good puncture site prior to the procedure [ 29 ]. The stallion is sedated and restrained in a stock.…”
Section: Examination Techniques Of the Stallion Scrotum And Its Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique may lead to some damage to the spermatozoa, such as separated heads, which will induce misinterpretation [25], and the staining can impair the visualization of small structural details [22]. Lengthening the Diff-Quick staining timings to 5 or 30 min [51,52] can lead to an observed slide quality that is similar to the reference method, but impairs its main interests: the speed and ease of realization. At present, the reference technique for fine morphology analysis is to dilute semen (1v/40v) in 37 • C formaldehyde 4%, to place a 5 µL drop on a 37 • C slide under a covering slide, and then to analyze 200 spermatozoa with contrast microscopy at ×1000 [6,25].…”
Section: Morphology Evaluation and Clinical Outcomesmentioning
confidence: 99%
“…Despite recent studies having shown that repeated testicular biopsy does not result in detrimental effects on prospective fertility [6,7], this invasive technique is not widely used among equine practitioners.…”
Section: Introductionmentioning
confidence: 99%